Superficial back line release versus trigger points release in chronic nonspecific low back pain patients - Zahran, Samah Saad; Atyia Esmail, Enas Mohammed; Fiyaz, Nadia Abd-Elazim; Ali Mohamed, Ahmed Essmat; Ahmed Badr, Sara Abd Elsemie; Elkhozamy, Hamed Mohammed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2024)
The aim of this study was to investigate the effect of Superficial back line (SBL) release on pain, Pressure Pain Threshold (PPT), lumbar function, lumbar ROM, and balance in chronic nonspecific low back pain (CNSLBP) patients. Additionally, it aims to compare the effect of SBL release versus myofascial trigger points (MTrPs) release on the same variables. This was a Randomized Controlled Trial (RCT) involving forty-eight male and female patients with CNSLBP. They were randomized via an online randomization web service into 3 groups: group A (n=16) received SBL release and exercises, group B (n=16) received MTrPs release and exercises, while group C (n=16) received exercises only. There were statistically significant improvements in all outcomes post-treatment in comparison to pre-treatment within the three groups (p<0.05). After treatment, significant differences emerged between the groups in pain, PPT, lumbar extension ROM, and left anterior balance (p < 0.05). Group A showed the most favorable results in pain reduction, lumbar extension ROM, and left anterior balance compared to groups B and C, while Group B demonstrated the most favorable results in PPT compared to groups A and C. In conclusion, SBL release and MTrPs release are effective in improving pain, lumbar function, MTrPs PPT, lumbar ROM, and balance in patients with CNSLBP. SBL release is particularly effective for pain, lumbar extension ROM, and left anterior balance, while MTrPs release is most effective for improving PPT.